The range of clinical manifestations of congenital glaucoma found in people seeking consultation at the Helmholtz National Medical Research Center of Eye Diseases - L. A. Katargina; A. A. Sorokin; N. N. Arestova; A. Yu. Panova; T. B. Kruglova; L. V. Kogoleva; T. V. Sudovskaya (Российский офтальмологический журнал)
Purpose: to analyze clinical and functional manifestations and the course of different stages of primary congenital glaucoma (CG) at different times of the disease onset, using the data of admissions to the Department of Eye Pathology in Children of the Helmholtz Research Center of Eye Diseases.Material and methods. 191 patients (320 eyes) with CG, of which 113 were children (191) eyes with primary congenital glaucoma (PCG) aged 1 month to 16 years, underwent standard ophthalmological examination (autorefractometry, visometry, biomicroscopy, ophthalmoscopy), electrophysiological examination (flash VEP, ganzfeld and flicker ERG) and echobiometry (axial eye length measurement).Results. A detailed clinical and functional characteristic of PCG, including structural and functional changes occurring at different stages. Most children with PСG showed advanced stages of the glaucomatous process: in cases where PСG was detected by 1 month of life, the advanced stages claimed 71.1 %, whilst the children diagnosed with PCG between 1 and 12 months of age, the advanced stages were found in 91.2 %. clinical manifestations were found to have variability, not always corresponding to the stages of the disease. In particular, we detected a correlation between disease progression and decreased VEP amplitude (p < 0.05), while no such correlation was found with respet to ERG parameters and VEP latency.Conclusion. Despite the fact that PCG is detected comparative early, the destructive glaucomatous eye damage leads to severe and often irreversible consequences. The timing of CG manifestation is determined by the degree of congenital abnormalities in the eye drainage system that, together with secondary structural changes of eyes (cornea, axial length, retina and ONH) entail a more severe prognosis of PCG in case of an early disease onset. New objective criteria are needed to assess the severity and prognosis of PCG, which is important for the preservation of visual functions, prevention of low vision and blindness.